Korean physicians’ attitudes toward the prenatal screening for fetal aneuploidy and implementation of non-invasive prenatal testing with cell-free fetal DNA - Kim, Soo Hyun; Kim, Kun Woo; Han, You Jung; Lee, Seung Mi; Lee, Mi-Young; Shim, Jae-Yoon; Cho, Geum Joon; Lee, Joon Ho; Oh, Soo-young; Kwon, Han-Sung; Cha, Dong Hyun; Ryu, Hyun Mee (Journal of genetic medicine, 2018)
Purpose: Physicians' attitudes may have a strong inḀuence on women’s decision regarding prenatal screening options. The aim of this study is to assess the physicians’ attitudes toward prenatal screening for fetal aneuploidy including non-invasive prenatal testing (NIPT) in South Korea.Materials and Methods: Questionnaires were distributed and collected at several obstetrics-gynecological conferences and meetings. The questionnaire included 31 multiple choice and 5 ἀll-in-the-blank questions. Seven questions requested physi-cians’ demographic information, 17 questions requested information about the NIPT with cell-free fetal DNA, and 12 ques-tions requested information about general prenatal screening practices.Results: Of the 203 obstetricians that completed the survey. In contrast with professional guidelines recommending the univer-sal offering of aneuploidy screening, only 53.7% answered that prenatal aneuploidy testing (screening and/or invasive diagnos-tic testing) should be offered to all pregnant women. Physicians tended to have positive attitudes toward the clinical applica-tion of NIPT as both primary and secondary screening methods for patients at high-risk for fetal trisomy. However, for patients at average-risk for fetal trisomy, physicians tended to have positive attitudes only as a secondary screening method. Physicians with more knowledge about NIPT were found to tend to inform their patients that the detection rate of NIPT is higher.Conclusion: This is the ἀrst study to investigate expert opinion on prenatal screening in South Korea. Education of physicians is essential to ensure responsible patient counseling, informed consent, and appropriate management after NIPT. KCI Citation Count: 0